Salmonella osteomyelitis: A rare differential diagnosis in osteolytic lesions around the knee - Khaled Hamed Salem (Elsevier, 2014)
Summary: Salmonella osteomyelitis in immunocompetent adults is uncommon. It usually has a diaphyseal location or present as spondylitis. Metaphyseal affection is extremely rare. A 51-year-old male presented with refractory knee pain. Plain X-rays showed a rounded osteolytic lesion in the proximal tibia without marginal sclerosis. A minimal C-reactive protein elevation and a normal leucocytic count were present. Further imaging raised suspicion of malignancy so that a biopsy was done. After fenestering the lesion, 15-ml turbid fluid was evacuated. Microbiological examination showed Salmonella enteritidis. Repeated debridements were done and antibiotic therapy with ciprofloxacin was initiated. The cavity was then filled with synthetic bone graft leading to progressive healing. Although rare, Salmonella bone infection usually lacks the typical periosteal reaction and the laboratory evidence of infection of pyogenic osteomyelitis. It should therefore be considered in the differential diagnosis of osteolytic neoplastic lesions. Keywords: Salmonella, osteomyelitis, Metaphyseal osteolytic lesions